NEURO-LINGUISTIC PROGRAMMING (NLP) AS A CUPPING MEDIA: A Living Hadith Discourse - MZ, Ahmad Murtaza; Isnaini, Subi Nur; Syahputra, Satria Tenun (RIWAYAH, 2022)
As a method of traditional medicine, cupping began to be in great demand by the public. Of course, this is an interesting phenomenon to be discussed. With the development of science, especially in the field of therapy, cupping is combined with modern communication techniques, namely Neuro-Linguistic Programming (NLP). The attempt to combine cupping with NLP is a novelty aspect in the study of cupping. This practice is carried out at Kopsen Rumah Sehat Thibbunnabawi, one of the few cupping clinics that use NLP techniques as a medium. Therefore, this article examines how Neuro-Linguistic Programming becomes a medium used in cupping practice. This research is a type of qualitative research using a phenomenological approach. Data collection methods used are interviews, observation, and documentation. Using the descriptive analysis method, there were five research informants, consisting of one therapist and four patients. This study found that: first, understanding of text internalization from cupping hadiths is still limited to the patient’s educational background or practical experience of each individual. Thus, various reasons from patients believe in cupping as a treatment. Second, the application of NLP as a cupping medium makes patients more comfortable and confident in doing therapy. Third, the application of NLP might be a solution so that patients who come are healed physically and psychologically.[Sebagai metode pengobatan tradisional, bekam mulai banyak diminati masyarakat. Tentu ini menjadi fenomena yang menarik untuk di diskusikan dan dikaji. Terlebih seiring berkembangnya ilmu pengetahuan terkhusus dalam bidang terapi, bekam dipadukan dengan teknik komunikasi modern yakni Neuro Linguistic Programming (NLP). Upaya untuk memadukan antara bekam dengan NLP merupakan aspek kebaharuan dalam ranah kajian mengenai bekam. Praktik seperti ini dilakukan di Kopsen Rumah Sehat Thibbunnabawi menjadi salah satu dari sedikit klinik bekam yang menggunakan teknik NLP sebagai medianya. Oleh karenanya, artikel ini mengkaji bagaimana Neuro Linguistic Programming menjadi media yang digunakan dalam praktik bekam. Penelitian ini merupakan jenis penelitian kualitatif dengan menggunakan pendekatan fenomenologis. Metode pengumpulan data yang digunakan yaitu wawancara, observasi, dan dokumentasi. Informan penelitian berjumlah 5 orang, terdiri dari 1 orang terapis, dan 4 pasien. Dengan menggunakan metode analisis deskriptif. Penelitian ini menemukan bahwa: pertama, pemahaman mengenai internalisasi teks dari hadis berbekam masih sebatas latar belakang pendidikan pasien ataupun pengalaman empiris dari tiap individu. Sehingga beragam alasan dari pasien meyakini bekam sebagai sebuah pengobatan. Kedua, pengaplikasian NLP sebagai media bekam menjadikan pasien lebih nyaman dan percaya diri untuk melakukan terapi. Ketiga, penerapan NLP mungkin bisa menjadi solusi agar pasien yang datang tidak hanya sembuh secara fisik namun sembuh pula dari segi psikologis.]